2014
DOI: 10.1515/secm-2013-0258
|View full text |Cite
|
Sign up to set email alerts
|

Modeling cement hydration by connecting a nucleation and growth mechanism with a diffusion mechanism. Part I: C3S hydration in dilute suspensions

Abstract: A particle-based C 3 S hydration model, which mathematically connects a nucleation and growth controlled mechanism with a diffusion controlled mechanism, is developed in this study. The model is first formulated and fitted with C 3 S hydration in stirred dilute suspensions in Part I where interactions between different particles can be ignored, and further developed and fitted with Portland cement paste hydration in Part II to account for inter-particle interactions. Excellent agreement was observed between ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 34 publications
1
6
1
Order By: Relevance
“…Therefore, unless one believes cement hydration never becomes diffusion controlled, the low diffusivity values should not be used against the second hypothesis mentioned above. The diffusion constant obtained from the model proposed in this study also seems to be independent of particle size, at least for C 3 S hydration in dilute suspensions [8] . While it is not yet possible to prove or disprove either hypothesis, the current study lends additional support to the second one.…”
Section: Introductionsupporting
confidence: 61%
See 4 more Smart Citations
“…Therefore, unless one believes cement hydration never becomes diffusion controlled, the low diffusivity values should not be used against the second hypothesis mentioned above. The diffusion constant obtained from the model proposed in this study also seems to be independent of particle size, at least for C 3 S hydration in dilute suspensions [8] . While it is not yet possible to prove or disprove either hypothesis, the current study lends additional support to the second one.…”
Section: Introductionsupporting
confidence: 61%
“…However, no modification to the model is necessary from this aspect as long as the hydration mechanism remains similar. This is especially true as it has already been shown that the shape of the growing nuclei does not significantly affect the fitting results [8] . For application to Portland cement paste hydration, the physical parameters (e.g., nucleation density, growth rate, and density of hydration product) shall be interpreted as the weighted average values of all hydration products growing on the surface of cement particles.…”
Section: Portland Cement Paste Hydrationmentioning
confidence: 81%
See 3 more Smart Citations